Capital Letter Pattern Recognition in Text to Speechby Way of Perceptron Algorithm - Wijaya, Novan (Knowledge Engineering and Data Science, 2018)
Computer vision is a data transformation retrieved or generated from webcam into another form in means of determining decision. All kinds of transformations are carried through to attain specific aims. One of the supporting techniques in implementing computer vision on a system is digital image processing as the objective of digital image processing is to transform digital-formatted picture so that it can be processed in computer. Computer vision and digital image processing can be implemented in a system of capital letter introduction and real-time handwriting reading on a whiteboard supported by artificial neural network mode “perceptron algorithm” used as a learning technique for the system to learn and recognize the letters. The way it works is captured in letter pattern using a webcam and generates a continuous image that is transformed into digital image form and processed using several techniques such as grayscale image, thresholding, and cropping image.